Biocidal effect of a hexane-soluble extract of Lippia graveolensKunth (Verbenaceae) (2018)
ABSTRACT: Lippia graveolens Kunth (Verbenaceae) is an economically important shrub known in Mexico as Oregano. In this work, the biocidal effect of the hexane extract of L. graveolens leaves was evaluated on two crop pests. Thus, larvaeof Spodoptera frugiperda were fed with mixtures of extract and artificial diet. The nematicidal activity was evaluated on juveniles of Meloidogyne javanica. Regarding S. frugiperda, quantitative differences between treatments and control were observed in dead pupae, surviving adults, and deformed adults (P < 0.05). All the surviving adults from the extract treatments were deformed. Nematicidal effect was registered, the LC50and LC90were 0.672 (0.654-0.690) and 0.965 (0.937-0.998) mg/mL respectively. The extract was characterized by NMR and GC-MS, being thymol the most abundant component (70.6%) in addition to carvacrol (22.8%). The results suggest the consideration of the hexane extract of L. graveolens leaves within the alternatives for the biological control of pests.